Energy reserve forming as the instrument of innovation development of enterprise - Strunin, Viktor; Strunina, Lesia (My University, 2014)
Nowadays the market conditions force enterprises for active innovation activity and development. One of the ways of such activity is providing effective energy policy to reach the best results and market positions. Such perspectives can be realized by creating proper energy reserve to provide smooth and effective functioning of the enterprise. The article is devoted to determining different aspect of enterprise's energy providing and energy reserve forming.
Keywords: енергозабезпечення підприємства; управління енергозабезпеченням; енергетичний потенціал підприємства; energy supply of the enterprise; energy potential of the enterprise; energy supply management; кафедра економіки праці та менеджменту